KEDUDUKAN GUBERNUR SEBAGAI WAKIL PEMERINTAH PUSAT DI DAERAH DALAM SISTEM KETATANEGARAAN INDONESIA - M. Arafat Hermana; Arie Elcaputera (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2020)
Abstract: Aside from being located as an autonomous region, it is also located as an administrative area; therefore, in addition to regulating the autonomous region, the Governor as the regional head also acts as the central representative in the regions. However, as the head of the region, the Governor is also responsible for regulating his autonomous region and also responsible to the people who elect him. The research objective is to discuss the constitutionality of the Governor's position as the representative of the central government in the region based on the 1945 Constitution of the Republic of Indonesia. The type of research used in this Studi is normative. The results showed that the Governor in carrying out his government in accordance with the mandate of the constitution performed its duties as regional head based on autonomy and assistance tasks. Based on the conclusions that can be drawn about whether the task is interpreted and the authority of the Governor is based on the principle of Deconcentration, the Position of the Governor is the Central Representative in the region and is an expansion of government in the administration of government.Keywords : Governor; Autonomy; Government